2015
DOI: 10.1002/tox.22179
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 2.45 GHz microwave radiation on the testicular inflammatory pathway biomarkers in young rats: The role of gallic acid

Abstract: The aim of this study was to investigate electromagnetic radiation (EMR) transmitted by wireless devices (2.45 GHz), which may cause physiopathological or ultrastructural changes, in the testes of rats. We addressed if the supplemental gallic acid (GA) may reduce these adverse effects. Six-week-old male Sprague Dawley rats were used in this study. Forty eight rats were equally divided into four groups, which were named: Sham, EMR only (EMR, 3 h day for 30 days), EMR + GA (30 mg/kg/daily), and GA (30 mg/kg/dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 51 publications
2
30
0
2
Order By: Relevance
“…Increased MDA levels in rat testes following RF-EMWs exposure was similarly reported in former studies [35,36].…”
Section: Discussionsupporting
confidence: 84%
“…Increased MDA levels in rat testes following RF-EMWs exposure was similarly reported in former studies [35,36].…”
Section: Discussionsupporting
confidence: 84%
“…Our result showed that VC treatment could improve sperm concentration and motility, increase serum testosterone concentration, decrease the percentage of abnormal spermatozoa and restore the normal testicular structure. Previous studies have reported that some phytochemicals including gallic acid has the potential to protect against oxidative stress in the testes and to reversed sperm abnormalities [25, 34]. Another study showed that selenium had beneficial effects on male infertility, wherein it improved the sperm count and motility, increased serum testosterone levels and alleviated the histopathological changes in the testes [3, 32, 33].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the total number of spermatogonia obviously declined after treatment with 5 Gy of irradiation [17]. The block for spermatogenesis progression and the induced abnormal sperm after RF exposure were also reported [7,8,18]. Recent study showed that the use of mobile phone hands-free devices lowered the RF exposure to the brain.…”
Section: Discussionmentioning
confidence: 99%